Siblings’ Experience on having Sibling with Autism Spectrum Disorder: A Literature Review - Livianinda Nur Malicha (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2020)
Autism Spectrum Disorder (ASD) is one of the special needs type that diagnosed children in the world. The prevalention of ASD case is increased over the years. ASD affects 1 in 59 children (Baio et al, 2018) and their families. The parents of child with ASD should be aware and give full of attention about the child’s condition. It is also including the environment around the child, like teacher, medical staffs, society, and sibling who lived together in daily activities. The presence of individual with ASD will affect the sibling relationship and gives both negatives and positives impact to their sibling. The purpose of this literature review is to summarize studies on what sibling relationships look like for a typically developing (TD) sibling of a child with an ASD. The search of e-literature was conducted to identify peer-reviewed articles published within the past 10 years concerning investigations on the role of sibling on individual with ASD, and sibling adjustment including the parental support. The electronic database used were: Proquest, SAGE Journals, and Science Direct. 31 studies were synthesized to include purpose, findings, and discussion relating the topic. The studies found that sibling, especially older brother/sister, affect better social adaptive and social functioning. The role of siblings also found in the intervention for individual with ASD. Besides the positive role of sibling, TD sibling of individual with ASD faced the challenges in adjustment. The difficulties made the TD siblings need support from parents and close friends that helped them forget about the stress associated with being a sibling.